Adaptive framework for long-term sensory home training: a feasibility study [data and source code] - Silvoni, Stefano; Desch, Simon; Beier, Florian; Bekrater-Bodmann, Robin; Löffler, Annette; Kleinböhl, Dieter; Tamascelli, Stefano; Flor, Herta (Universität, 2024)
This data and source code collection enables any user to reproduce the results of the feasibility study published in Silvoni et al. (2024). The access to the data.zip file can be granted upon a reasonable request to the licensor at the following e-mail: herta.florzi-mannheim.de (or stefano.silvoni@zi-mannheim.de). The training datasets collected during the feasibility study can be read and analysed. The source code can be used to build the Android application which was used to collect the training data (an executable version of the application is also available). However, because it is based on specific and custom-built hardware devices, the reader is invited to contact the licensor for further details. For details concerning the datasets and the application, please, see the provided README.txt file. The main aim of the feasibility study was to determine whether an adaptive framework based on operant learning principles and on brain-plasticity-based training programs is able to promote learning over a long period of time at home of the user, and whether indicators of learning can be derived from individual training data. The study represents the practicability of the methods which can form the bases to design training procedures engaging simple and complex abilities such as sensory perception, sensory integration, motor control and testing of complex psychometric functions.